Production of Hydrogen Sulphide and Other Volatile Sulphides by Spoilage Bacteria from Fish - Thampuran, Nirmala; K., Mahadeva Iyer (Fishery Technology, 2025)
The performance of live agar media for enumerating hydrogen sulphide producing, spoilage bacteria in marine fishes was evaluated and the results are discussed Comparison of filter paper strip method using two reagents lead acetate and dithio bisnitro benzoic acid (DTNB), with the iron agar slants showed that the lead acetate paper strips were more sensitive than other methods for detecting minute quantities of hydrogen sulphide. The nature and concentration of the substrate were found to influence the production of hydrogen sulphide. Majority of the isolated cultures attacked cysteine and produced hydrogen sulphide alone. Bacterial isolates which produced volatile sulphides other than hydrogen sulphide were very few and the volatile sulphides were produced when methionine was used as the substrate. The hydrogen sulphide producers from fish belonged to genera Aeromonas, Vibrio, Alteromonas, Enterobacteriaceae, Pseudomonas, Acinetobacter, Moraxella etc.